2019
DOI: 10.1001/jamaoto.2019.0742
|View full text |Cite
|
Sign up to set email alerts
|

Association of Air Pollution With Increased Risk of Peritonsillar Abscess Formation

Abstract: IMPORTANCE Several studies reported an association between peritonsillar abscess formation and climate conditions, including seasonal changes; however, the results were inconsistent.OBJECTIVE To evaluate the association between meteorological conditions and/or air pollution and peritonsillar abscess formation. DESIGN, SETTING, AND PARTICIPANTSIn this nested case-control study, 3819 participants with peritonsillar abscesses were matched (1:4) for age, sex, income, region of residence, hypertension, diabetes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 28 publications
0
23
0
3
Order By: Relevance
“…All procedures were followed in accordance with the relevant guidelines. The Korean National Health Insurance Service-Health Screening Cohort (NHIS-HEALS), meteorological, and air pollution data were used (S1 description) [20][21][22] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All procedures were followed in accordance with the relevant guidelines. The Korean National Health Insurance Service-Health Screening Cohort (NHIS-HEALS), meteorological, and air pollution data were used (S1 description) [20][21][22] .…”
Section: Methodsmentioning
confidence: 99%
“…Participants with ischemic heart disease were selected from 514,866 patients with 497,931,549 medical claim codes (n = 2239) [20][21][22] . Among these participants, individuals were excluded if they were diagnosed with ischemic heart disease before 2004 (n = 80) to track previous exposure to meteorological factors in the last 2 years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many studies on the impact of environmental conditions on PTA, although the results were not consistent. 8 A study enrolling 528 patients with PTA showed that this disease was more likely to occur in warmer months. 9 Nevertheless, some other researchers recognized that PTA patients exhibited an even distribution over the year.…”
Section: Introductionmentioning
confidence: 99%